Developing unity: Upholding the oneness God gives me with others - Churches Alive (U.S.A, 1993)
You are linked to everyone in the world. With some, the relationship is intense. With others, it is remote and imperceptible.In Developing Unity you will be exploring the five levels of human relationship-from the most intimate one of marriage to the broadest one of humankind.The more you understand these levels of the relationship as a part of God's design, the more you'll be able to appreciate them and appropriate His strength to uphold them as He intends.
Keywords: Love one another series